2008
DOI: 10.2174/157341108784911325
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Stripping Voltammetry of Environmental Carcinogens

Abstract: This review describes our recent results regarding adsorptive stripping voltammetric determination of submicromolar and nanomolar concentrations of various environmentally important chemical carcinogens using both traditional (hanging mercury drop electrode, carbon paste electrode) and non-traditional types of electrodes (solid amalgam electrodes, glassy carbon paste electrodes, carbon ink film electrodes, solid composite electrodes). The review concentrates on our own results in the context of the general dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 31 publications
(44 reference statements)
2
40
0
Order By: Relevance
“…The experimental value of the slope of this curve was found to be about 55 mV per unit pH in the studied pH range. The slope is very close to the theoretical value of 59 mV per unit pH required under assumption of the 2e -/2H + or 4e -/4H + process 25,26 of the electroreduction of MKST. Based on the literature, the equation 1 was used to find the ratio of the number of protons to the number of electrons (∂/n) in the electrode mechanism: .…”
Section: Resultssupporting
confidence: 81%
“…The experimental value of the slope of this curve was found to be about 55 mV per unit pH in the studied pH range. The slope is very close to the theoretical value of 59 mV per unit pH required under assumption of the 2e -/2H + or 4e -/4H + process 25,26 of the electroreduction of MKST. Based on the literature, the equation 1 was used to find the ratio of the number of protons to the number of electrons (∂/n) in the electrode mechanism: .…”
Section: Resultssupporting
confidence: 81%
“…Especially, adsorptive stripping analysis greatly enhances the scope of stripping measurements toward numerous low amounts of organic compounds. Short adsorption times (1-5 min) result in a very effective interfacial accumulation [22][23][24][25][26][27][28][29].…”
Section: Electroanalytical Determination Of Tsmentioning
confidence: 99%
“…Reviewing the literature revealed that, up to the present time, there is no square-wave cathodic stripping voltammetric method using mercury electrode to assay of TS in pharmaceutical formulation and biological samples. The voltammetric techniques, such as cyclic voltammetry, differential pulse voltammetry and square-wave voltammetry have been proved to be very sensitive for the determination of organic molecules including drugs and related molecules in pharmaceutical dosage forms and biological fluids [22][23][24][25][26]. These methods are faster, easier to be operated and cheaper than spectroscopic and chromatographic methods.…”
Section: Introductionmentioning
confidence: 99%
“…A further increase in the sensitivity of the determination could be achieved by adsorptive accumulation of the test substance on the m-AgSAE surface [24]. It has been proven that only 2-NF gave a significantly increased voltammetric response in dependence on the time of accumulation (t acc ).…”
Section: Voltammetric Determination Of the Test Substancesmentioning
confidence: 99%
“…The easy electrochemical reduction of nitro groups at the aromatic ring, whose mechanism is discussed in [22], permits very sensitive determinations of a number of genotoxic and ecotoxic nitro compounds using modern voltammetric techniques such as differential pulse voltammetry (DPV) at a hanging mercury drop electrode (HMDE) [23] and adsorptive stripping voltammetry (AdSV) at HMDE [24]. Nevertheless, due to increasing fears of liquid mercury toxicity during the last decades [25], which has resulted in the "mercury phobia" [26], attention is paid to the development of solid electrodes (e.g., solid amalgam electrodes [27,28], solid composite electrodes [29], carbon paste electrodes [30] or boron-doped diamond film electrodes [31]), which can also be used to determine various nitro compounds.…”
Section: Introductionmentioning
confidence: 99%